2015
DOI: 10.1186/s13075-015-0574-9
|View full text |Cite
|
Sign up to set email alerts
|

CYB5A polymorphism increases androgens and reduces risk of rheumatoid arthritis in women

Abstract: IntroductionRheumatoid arthritis (RA) is characterized by decreased androgen levels, which was the first hormonal abnormality described. Several studies indicated that steroidogenesis is directed towards endogenous glucocorticoids at the expense of androgens. The decisive step governing androgen synthesis is the 17,20-lyase activity of the CYP17A1 gene-encoded enzyme cytochrome P450 17A1. Here, we focused on the role in RA of the critical cofactor for 17,20-lyase activity, cytochrome b5, encoded by the CYB5A g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 55 publications
0
21
0
1
Order By: Relevance
“…We found a strong contribution of hormone-responsive genes to several diseases and anthropometric traits, with examples of sex-interaction in this contribution (hypothesis 4). Recently, a gene involved in androgen synthesis was associated with RA (Stark et al 2015), and we show that androgen-responsive genes across the genome are enriched for association signal and sex differences. Although estrogen biology has been associated with comorbidities of T1D (Ryba et al 2011;Ryba-Stanisławowska et al 2014;Słomiński et al 2015), our results are the first to suggest a global impact on risk.…”
Section: Discussionmentioning
confidence: 71%
“…We found a strong contribution of hormone-responsive genes to several diseases and anthropometric traits, with examples of sex-interaction in this contribution (hypothesis 4). Recently, a gene involved in androgen synthesis was associated with RA (Stark et al 2015), and we show that androgen-responsive genes across the genome are enriched for association signal and sex differences. Although estrogen biology has been associated with comorbidities of T1D (Ryba et al 2011;Ryba-Stanisławowska et al 2014;Słomiński et al 2015), our results are the first to suggest a global impact on risk.…”
Section: Discussionmentioning
confidence: 71%
“…Two notable exceptions to this include women who inherited particular polymorphisms resulting in higher or lower androgen levels correlating with protection from disease or exacerbation, respectively. First, women predisposed to produce androgens in greater concentrations due to inheritance of a polymorphism in the CYB5A gene are protected from developing RA characterized by RF and antibodies to citrullinated proteins ( 141 ); and, second, women with lower serum androgens are more likely to develop a type of RA that is not responsive to combination therapy consisting of nonsteroidal anti-inflammatory drugs, low-dose prednisolone, methotrexate, and more than one of several other disease modifying anti-rheumatic drugs ( 142 ).…”
Section: Androgens In Autoimmunitymentioning
confidence: 99%
“…Several genes outside the HLA region, including Stat4, the TRAF1-C5 locus, and PTPN22, have been reported to be associated with activation and progression of inflammation in RA [58][59][60][61][62]. Sex disparities in genetic susceptibility to RA are understudied, and only a polymorphism in the Cyb5a gene, which is related to androgen synthesis, has been found to be associated with risk for RA in women but not in men [63]. Recent studies have also suggested a role for epigenetic modifications in the activation and aggressiveness of synovial fibroblasts [64][65][66][67] and the X-encoded genes, Timp1 and IL-9R in RA [68].…”
Section: Discussionmentioning
confidence: 99%